The dehydration- and ABA-inducible germin-like protein CpGLP1 from Craterostigma plantagineum has SOD activity and may contribute to cell wall integrity during desiccation - Giarola, Valentino (Planta, 2020)
MAIN CONCLUSION: CpGLP1 belongs to the large group of germin-like proteins and comprises a cell wall-localized protein which has superoxide dismutase activity and may contribute towards ROS metabolism and cell wall folding during desiccation. ABSTRACT: The plant cell wall is a dynamic matrix and its plasticity is essential for cell growth and processing of environmental signals to cope with stresses. A few so-called resurrection plants like Craterostigma plantagineum survive desiccation by implementing protection mechanisms. In C. plantagineum, the cell wall shrinks and folds upon desiccation to avoid mechanical and oxidative damage which contributes to cell integrity. Despite the high toxic potential, ROS are important molecules for cell wall remodeling processes as they participate in enzymatic reactions and act as signaling molecules. Here we analyzed the C. plantagineum germin-like protein 1 (CpGLP1) to understand its contribution to cell wall folding and desiccation tolerance. The analysis of the CpGLP1 sequence showed that this protein does not fit into the current GLP classification and forms a new group within the Linderniaceae. CpGLP1 transcripts accumulate in leaves in response to dehydration and ABA, and mannitol treatments transiently induce CpGLP1 transcript accumulation supporting the participation of CpGLP1 in desiccation-related processes. CpGLP1 protein from cell wall protein extracts followed transcript accumulation and protein preparations from bacteria overexpressing CpGLP1 showed SOD activity. In agreement with cell wall localization, CpGLP1 interacts with pectins which have not been reported for GLP proteins. Our data support a role for CpGLP1 in the ROS metabolism related to the control of cell wall plasticity during desiccation in C. plantagineum. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00425-020-03485-0) contains supplementary material, which is available to authorized users.